(untitled) (Journal of Philosophy Culture and Political Science, 2019)
It has been shown that unsatisfactory state of post-Soviet higher education is largely connected with the fact that the fundamental principles of von Humboldt, which ensured the formation of classical university education at the end of the 19th century, are no longer realized in modern conditions. First of all, due to the fact of widespread higher education, it is only possible to speak formally about interconnection between academic freedom, education and science within the walls of the overwhelming majority of post-Soviet universities. Over the past 150 years, the workload of professors has increased on average from 4 to 30 hours per week, which excludes the realization of academic freedom. This fact reflects systemic crisis in higher education of industrial era and significant difficulties in transition to post-industrial university. It has been shown that to overcome the prevailing negative trends, first of all, it requires the formation of adequate ideas of post-industrial higher education economics as well as systemic counteraction to transitional diseases, which include the flourishing of pseudoscience (especially in areas related to telecommunication technologies), as well as corruption, for which the pseudo-science is working as breeding ground. Key words: Pseudoscience, Humboldt principles, university education, telecommunication technologies, study load, post-industrial high school.